In-house device fabrication for multiple blood sampling of adult zebrafish, Danio rerio - Abdullah, Nur Raihan; Sharif, Faez; Azizan, Nur Hafizah; Wan-Mohtar, Wan Abd Al-Qadr Imad; Chowdhury, Ahmed Jalal Khan; Mohd Nasir, Mohd Hamzah (Elsevier Inc., 2024)
Multiple blood collection from an adult Danio rerio is important in most of metabolic studies. The method allows researcher to profile the metabolic dynamic from an individual fishes, which contribute to a high resolution of dataset. Currently, several devices have been developed for the purpose of blood withdrawal from Danio rerio. Limited accessibility to it hindering the log phase development of Danio rerio based studies. This study shows that the multiple blood collection from an adult Danio rerio can be achieved to the highest survival rate (94.75 %) using the in-house fabricated Z-fish needle. The fabricated device is cheaper and can be accessible in any developing Danio rerio laboratory. The device contains two main components: (i) the sampling syringe and (ii) the micro-capillary needle. Both components play its important role in contributing to the successful blood collection procedure.